Penerapan Metode Regresi Linier Sederhana Untuk Prediksi Jumlah Persediaan Pestisida - Annur, Haditsah; Sudirman Melangi; Andri Setiawan (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2024)
Abstract - Forecasting is needed to make things easier for CV. Anak Tani predict how much Roger's pesticide supply will be needed in the following month, so that they do not experience the delivery of the amount of Roger's pesticide supply in the following month. The simple linear regression method is a forecasting method that uses two factors so that it can determine maximum results. The problem faced is that there is often a buildup of pesticide 1 liter Roger 480SL inventory CV. Anak Tani. The aim is to find out the results of applying a simple linear regression method to predict the amount of inventory of 1 Liter Roger 480SL pesticide located at CV. Anak Tani. The results obtained by the mean absoluter percentage error (MAPE) were tested with the 2022 data obtained, namely 7.80%, so it can be concluded that this system is effective to use.Key words: Forecasting, Inventory, Pesticide Roger 480sl 1 Liter, Mape